Using eye-tracking in applied linguistics and second language research - Conklin, Kathy; Pellicer-Sánchez, Ana (SAGE Publications, 2016)
With eye-tracking technology the eye is thought to give researchers a window into the mind. Importantly, eye-tracking has significant advantages over traditional online processing measures: chiefly that it allows for more ‘natural’ processing as it does not require a secondary task, and that it provides a very rich moment-to-moment data source. In recognition of the technology’s benefits, an ever increasing number of researchers in applied linguistics and second language research are beginning to use it. As eye-tracking gains traction in the field, it is important to ensure that it is established in an empirically sound fashion. To do this it is important for the field to come to an understanding about what eye-tracking is, what eye-tracking measures tell us, what it can be used for, and what different eye-tracking systems can and cannot do. Further, it is important to establish guidelines for designing sound research studies using the technology. The goal of the current review is to begin to address these issues.